2005
DOI: 10.1002/cbf.1307
|View full text |Cite
|
Sign up to set email alerts
|

Influence of indole acetic acid on antioxidant levels and enzyme activities of glucose metabolism in rat liver

Abstract: Indole acetic acid (IAA) is an auxin and can be synthesized in animals. This compound is metabolized in vitro by peroxidase, producing reactive oxygen species. The toxic effect of indole acetic acid in leukocytes is associated with peroxidase activities and these processes have been implicated in activation of glucose and glutamine metabolism. However, studies in vitro have shown that IAA, in absence of peroxidase, is an antioxidant almost as high in potency as those of other indolic compounds. The purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 36 publications
(39 reference statements)
1
9
0
4
Order By: Relevance
“…Recent studies shown that orally or subcutaneous IAA has no toxic action on rats leukocytes measured by analyzing the DNA integrity, membrane integrity, and enzyme activities. [12][13][14] However, the genotoxic carcinogen DEN induced extensive DNA damage 42 in accordance with the present study. Moreover, IAA was partially efficient in providing protection to DENinduction of DNA fragmentation; similarly, guarana has a protective effect against DEN-induced DNA damage in mouse liver.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Recent studies shown that orally or subcutaneous IAA has no toxic action on rats leukocytes measured by analyzing the DNA integrity, membrane integrity, and enzyme activities. [12][13][14] However, the genotoxic carcinogen DEN induced extensive DNA damage 42 in accordance with the present study. Moreover, IAA was partially efficient in providing protection to DENinduction of DNA fragmentation; similarly, guarana has a protective effect against DEN-induced DNA damage in mouse liver.…”
Section: Discussionsupporting
confidence: 92%
“…11 Recent studies have shown that oral or subcutaneous administration of IAA can promote a possible beneficial effect by increasing the phagocytic capacity of rat neutrophils. 12,13 This auxin administration does not have a deleterious effect on leukocytes and liver of rats 14 and the IAA does not have an effect on metabolic enzyme activities in mice kidneys. 15 The prevention of several diseases by many natural substances has been associated with the antioxidant action of these compounds upon depletion of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 95%
“…19 Recent studies have shown that subcutaneous IAA promotes an increase in phagocytic capacity, is accompanied by alteration in hydrogen peroxide production in neutrophils, but does not show a pro-oxidant effect in leukocytes 20 or liver. 21 The information above led us to study the effect of IAA administered subcutaneously and by gavage to rats at low doses (equal to or less than 40 mg of IAA per kg of body mass) on neutrophil functions and cell death of neutrophils and lymphocytes. This study was undertaken to investigate the possible utilization of indole acetic acid as a diet supplement for animals.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of peroxidase IAA acts as a prooxidant substance and generates oxidative stress by an increased formation of reactive oxygen species (ROS) . However, studies have showed that oral or subcutaneous administration of IAA increased the phagocytic capacity of neutrophil and do not have deleterious effect of rat livers and mice kidneys . Moreover, IAA showed potent antioxidant effects and warned the mice livers against hepatocarcinoma induced by N‐nitrosodietilamina (DEN) .…”
Section: Introductionmentioning
confidence: 99%